Persona in Social Media: A Case Study on Baim Paula Youtube Channel - Aidatul Chusna (Universitas Sanata Dharma, 2021)
Social media enables its users to participate in creating and sharing media contents through their accounts; thus, it gives opportunity to gain popularity for anyone, including celebrity. This paper is aimed at revealing celebrities’ strategy to increase and maintain their popularity by constructing self-image through social media. Videos from Baim Paula youtube channel are selected as the main data of the analysis, considering Baim Wong’s success as celebrity and content creator. Using textual approach, the vidoes created and shared are analized as a cultural text which demonstrates celebrities’ self-representation in social media. The result shows that Baim Wong performs various self- images through his videos contents. His prank videos indirectly indicate authenticity and honesty entitled to Baim Wong’s image, as a strategy to create closeness to his fans. He also construcs an altruistic persona by giving presents and/or money to his pranked targets. Another self-representation is seen in videos about his daily activities with family and friends. Through these videos, Baim Wong constructs his image as a family man. The persona performed in social media has successfully attracted more fans/ subscribers and enhanced his fame. Subsequently, it generates profit not only from his YouTube channel, but also from advertising agencies and TV stations that hire him.